The Transformation Of Productive Zakat As An Empowerment Strategy: A Study Of The Mahyani Program And Baznas Housing Rehabilitation Initiative In East Lombok Regency - Wan Syurur Feiruz Algadri (Universitas Islam Darul 'ulum Lamongan, 2026)
Extreme poverty demands a paradigm shift in zakat fund management from a purely charitable approach to sustainable productive empowerment. This study aims to analyze the implementation mechanism and the impact of the Mahyani Program (new housing construction) and Housing Rehabilitation initiated by BAZNAS East Lombok Regency on the socio-economic empowerment of mustahik. This study utilizes a descriptive qualitative method with a case study approach. Primary and secondary data collection were conducted through field observations, in-depth interviews with amil and mustahik, and documentation studies, which were subsequently analyzed using an interactive model. The results indicate that BAZNAS East Lombok successfully overcame fiscal limitations through a collaborative governance scheme (blended finance), synergizing profit-sharing funds from BAZNAS NTB Province and CSR funds from Bank NTB Syariah. Furthermore, the findings confirm that housing infrastructure intervention is not merely consumptive zakat but a fundamental prerequisite that transforms dwellings into productive assets (Home-Based Enterprises). The integration of physical construction with business capital stimulus, such as the Z-Kuliner program, has proven effective in breaking socio-health vulnerabilities and comprehensively fostering mustahik economic independence, fully aligning with Maqashid Sharia principles.